Tensile capacity of FRP anchors in connecting FRP and TRM sheets to concrete. (1st January 2015) - Bournas, Dionysios A.; Pavese, Alberto; Tizani, Walid
Highlights: Effectiveness of carbon fiber spikes anchors for EB FRP and TRM sheets into concrete. Experimental work measured the tensile resistance of the anchors. Experiments varied size and no. of anchors, bonding agent, type and amount of EB reinforcement. The spikes provided effective anchorage preventing premature delamination. Abstract: This paper investigates the effectiveness of carbon fiber spike anchors as a means of anchoring externally bonded (EB) fiber-reinforced polymers (FRP) and textile reinforced mortar (TRM) sheets into concrete. The investigation employs experimental work, which includes reinforced concrete (RC) columns strengthened with various configurations of EB FRP and TRM sheets connected to RC footings via carbon fiber spike anchors. The fiber spikes have two parts: the anchor part and the fan part. The anchor part is a bar-type dowel component that is epoxy pre-impregnated and inserted into epoxy filled holes within the footing. The fan part was impregnated in-situ and fanned out over and bonded to the EB reinforcement of the column. The connections were tested by pulling the columns upwards, thus applying tensile forces to the connection system. The direct tensile capacity of the anchors was determined for a number of variables including the size and number of anchors, the bonding agent and the type and amount of EB reinforcement. It is concluded that, with appropriate anchorage into concrete, the carbon fiber spike anchor is an effective anchorage system, and therefore, could be used in a range of strengthening applications to prevent premature delamination of FRP and TRM sheets from concrete surfaces.